A new role for Zinc limitation in bacterial pathogenicity: modulation of α-hemolysin from uropathogenic Escherichia coli - Elsa Velasco (Nature Portfolio, 2018)
Abstract Metal limitation is a common situation during infection and can have profound effects on the pathogen’s success. In this report, we examine the role of zinc limitation in the expression of a virulence factor in uropathogenic Escherichia coli. The pyelonephritis isolate J96 carries two hlyCABD operons that encode the RTX toxin α-hemolysin. While the coding regions of both operons are largely conserved, the upstream sequences, including the promoters, are unrelated. We show here that the two hlyCABD operons are differently regulated. The hly II operon is efficiently silenced in the presence of zinc and highly expressed when zinc is limited. In contrast, the hly I operon does not respond to zinc limitation. Genetic studies reveal that zinc-responsive regulation of the hly II operon is controlled by the Zur metalloregulatory protein. A Zur binding site was identified in the promoter sequence of the hly II operon, and we observe direct binding of Zur to this promoter region. Moreover, we find that Zur regulation of the hly II operon modulates the ability of E. coli J96 to induce a cytotoxic response in host cell lines in culture. Our report constitutes the first description of the involvement of the zinc-sensing protein Zur in directly modulating the expression of a virulence factor in bacteria.